Effect of epidural methylprednisolone on post-operative pain and length of hospital stay in patients undergoing lumbar microdiscectomy. Issue 5 (October 2015) - Aljabi, Yasser; El-Shawarby, Amr; Cawley, Derek T.; Aherne, Thomas
Abstract Background & aim Intraoperative epidural corticosteroids have been used to decrease post-operative pain post-discectomy. The objective of this study is to assess the efficacy of epidural corticosteroids on post-operative pain and length of post-operative hospital stay in patients undergoing unilateral lumbar microdiscectomy. Methods 150 consecutively treated, comparable patients with unilateral lumbar disc herniation were prospectively allocated randomly to receive either a sponge soaked in epidural corticosteroids or saline at the end of the operative procedure. The intensity of spontaneous pain was quantified by using the Oswestry low back pain index pre-operatively, at discharge, at week 1 follow-up and at 1st month of follow up. At the same intervals, each patient underwent the passive straight leg-raising test (PSLRT) and Visual Analogue Scale (VAS) testing. The duration of hospital stay, time taken to return to daily life activities and quantity of analgesia consumed post-operatively were also recorded. Results The mean hospital stay was 1.3 ± 0.9 days in the corticosteroids group (group 1) compared to 3.2 ± 1.2 in the control group (group 2). The mean interval until return to daily life activities was 6.7 ± 2.1 days in group 1 versus 9.6 ± 4.1 days in group 2. No statistically significant difference was measured between the steroid-treated and control groups when the data were stratified for sex, age, and site of disc herniation. Differences in the OLBI scores were statistically significant at all post-operative intervals. At baseline (preoperatively), group 1 (DepoMedrol™ group) had an average score of 72.3% (±2.6%) compared to 74.6% (±3.1%) in group 2 (Control group) (P = 0.45). At discharge, OLBI scores declined to 49.7% (±4.5%) in group 1 compared to 63.5% (±3.9%) in group 2 (P = 0.034). At week 1 follow-up, OLBI scores further declined to 41.3% (±2.9%) in group 1 versus 54.2% (±5.3%) in group 2 (P = 0.014). After one month of follow-up, OLBI scores were 34.1% (±6.7%) in group 1 and 42.6% (±4.1%) in group 2 (P = 0.004). Results of VAS and PSLRT are also documented in the manuscript. The mean postoperative analgesic medications consumed was 15.6 ± 1.9 mg of morphine equivalent in the corticosteroid group versus 10.3 ± 1.8 mg of morphine equivalent in the control group. No complications of treatment occurred in either groups. Conclusion Intraoperative application of epidural corticosteroids, Depomedrol, significantly reduces post-operative pain, length of post-operative stay and duration to return to daily living activities following lumbar discectomy.